In the shadow of the moon : America, Russia, and the hidden history of the space race - Cherrix, Amy E. (Balzer+Bray, 2021)
Explores the history of the Space Race between the United States and the U.S.S.R. through the lives of the principle engineers on either side of the Cold War--for the U.S. was Wernher von Braun, a former Nazi scientist; for the Russians, there was Sergei Korolev, who once was jailed for crimes against his own country.